Ambulatory microdose induction of buprenorphine‐naloxone in two adolescent patients with sickle cell disease. Issue 1 (27th October 2020) - Buchheit, Bradley M.; Joslin, Timothy; Turner, Helen N.; Wong, Trisha E.
Abstract: Sickle cell disease (SCD) is a hematologic disorder defined by presence of sickle‐shaped red blood cells that can occlude blood vessels and cause tissue ischemia and pain. Treating SCD pain adequately and safely is difficult given today's opioid climate. Buprenorphine‐naloxone has been described as an alternative option to treat chronic pain in the adult literature; however, it historically required discontinuation of full‐agonist opioids before initiation, resulting in opioid withdrawal. Herein we present two adolescents with SCD who successfully weaned off large doses of full‐agonist opioids by using microdose induction of buprenorphine‐naloxone in clinic, without experiencing significant opioid withdrawal. Ambulatory microdose induction may remove hurdles that otherwise would discourage patients from trying this regimen while still controlling pain safely.